Defining the Distinct Skin and Gut Microbiomes of the Northern Pike (Esox lucius) - Reinhart, Elizabeth M.; Korry, Benjamin J.; Rowan-Nash, Aislinn D.; Belenky, Peter (Frontiers in Microbiology, 2019)
The microbiome of freshwater fish has important implications for both commercial and recreational fishing as it is known to have significant impacts on host heath and susceptibility to disease. The aqueous environment serves as a possible avenue for continuous introduction of microbes to an animal host, but little is known about how the surrounding microbiota contribute to piscine microbiomes. To better understand the composition of the fish microbiome exposed to the natural environment, we profiled the microbial composition of the gut and the skin mucosal surface (SMS) of northern pike (Esox lucius) and the surrounding river water. We collected fish samples from eight sites along the Chochocouane River in Quebec, Canada and analyzed the microbial composition via 16S rRNA sequencing. Our results reveal robust taxonomic differences between the SMS and the gut, indicating a divergence between the microbiomes. The gut community was characterized by a lower alpha diversity compared to the SMS and a large proportion of Cetobacterium, a genus previously linked to carnivorous species. On the other hand, the SMS was more similar to the water than the gut at the family level but divergent at lower taxonomic levels, with fewer than 30% of OTUs shared between the SMS and water. In total, our results suggest the establishment of distinct communities across the two fish sites and a distinct separation from the microbes in surrounding waters. These data indicate that despite continuous exposure to water, pike are able to establish and maintain unique microbial communities.